2017
DOI: 10.1039/c7nj02254a
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-N,N,N-trioctylammonium chloride as a novel and green corrosion inhibitor for mild steel in an acid chloride medium: electrochemical, DFT and MD studies

Abstract: In the present work, N-methyl-N,N,N-trioctylammonium chloride (Aliquat 336) has been evaluated as a green and novel corrosion inhibitor for mild steel in a 1 M HCl solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 60 publications
2
48
0
Order By: Relevance
“…[32][33][34] In strong corrosive electrolytic media like HCl, H 2 SO 4 , HNO 3 and H 3 PO 4 , the heteroatoms of inhibitor molecules (N, O, S, and P) easily undergo protonation because of their unshared electron pairs. [4,[35][36][37] Therefore, in such electrolytic media, inhibitor molecules (or heteroatoms) exist in the cationic/ protonated forms. [38][39][40] On the other hand, metallic surface become negatively charged because of the adsorption of counterions of electrolytes on the positively charged metallic surface.…”
Section: Interactions: Coordination Chemistrymentioning
confidence: 99%
“…[32][33][34] In strong corrosive electrolytic media like HCl, H 2 SO 4 , HNO 3 and H 3 PO 4 , the heteroatoms of inhibitor molecules (N, O, S, and P) easily undergo protonation because of their unshared electron pairs. [4,[35][36][37] Therefore, in such electrolytic media, inhibitor molecules (or heteroatoms) exist in the cationic/ protonated forms. [38][39][40] On the other hand, metallic surface become negatively charged because of the adsorption of counterions of electrolytes on the positively charged metallic surface.…”
Section: Interactions: Coordination Chemistrymentioning
confidence: 99%
“…The appositively charged species interact from each other using physisorption mechanism. On this basis, it can be concluded that DGEBA‐polyaminoamide interacts with the metallic surface by a combination of physisorption as well as chemisorption mechanisms …”
Section: Resultsmentioning
confidence: 99%
“…It is important to mention that organic coatings such as DGEBA‐polyaminoamide can interact with the metallic surface using their chemisorption or physisorption mechanism. Generally, electron‐rich centers such as heteroatoms of polar functional groups and conjugated π‐electrons of multiple bonds favor the chemisorption mechanism . These electron‐rich centers transfer their electrons into the d‐orbital of surface metallic atoms through coordination (chemical bonding).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations